Challenges faced by students during the implementation of OLD amidst covid-19 pandemic: a case study of UiTM Pahang / Mazni Muslim … [et al.] - Muslim, Mazni; Bakar, Sulaila; Razali, Azlini; Mohamad, Zulkefli (Universiti Teknologi MARA, Pahang, 2022)
This paper examines the challenges students faced in ensuring effective learning process while incorporating digital technologies in the middle of Covid-19 pandemic. It was found that efforts of the Malaysian government, universities and educators to promote the Open and Distance Learning (ODL) were constrained and limited by numerous obstacles faced by the students. The main focus of this study was to identify the students’ setbacks to their learning outcomes. Questionnaires through Google Forms were distributed to 92 students from four different faculties in Jengka and Raub campuses. The objective was to find answers to these three questions: students’ physical obstacles, effectiveness of ODL and students’ emotional challenges. The findings concluded that these students were overwhelmed by both their coursework and also their lecturers. The lecturers’ expectation also played a big role in this difficult situation, forcing students to feel worried and pressured. Nevertheless, this study also found other contributing factors that impede their learning outcome; networking factors, family support and the students’ perspective towards their studies. Based on the data collected, in-depth analysis, conclusions and recommendations were made in the hope that our findings could help them become better students, and the educators to be more reasonable.